Raltegravir plus Two Nucleoside Analogues as Combination Antiretroviral Therapy in HIV-Infected Patients who Require Cancer Chemotherapy. Issue 7 (October 2015) - Casado, José L; Machuca, Isabel; Bañón, Sara; Moreno, Ana; Moltó, José; Rodriguez, Miguel A
Background: There are few data on the best combination antiretroviral therapy in patients with HIV infection who need cancer chemotherapy because of drug–drug interactions and increased risk of toxic effects. Methods: We evaluated the safety, efficacy and interactions of a raltegravir (RAL)-based regimen in 30 HIV-infected patients who received antineoplastic agents. Results: A total of 17 patients had a non-AIDS-defining malignancy (7 with Hodgkin disease) and 13 had an HIV-related cancer (9 non-Hodgkin lymphoma, 2 Kaposi sarcoma and 2 anal cancer). Overall, they received 49 cycles of chemotherapy with 19 different antineoplastic drugs, including antimetabolites in 4 patients (5-FU, gemcitabine), alkylating agents in 10 cases (cyclophosphamide, ifosfamide), vinca alkaloids in 17 patients (vincristine, vinblastine), anti-tumour antibiotics in 18 cases (doxorubicin), cisplatin or carboplatin in 6, and monoclonal antibodies in 13 patients (rituximab, trastuzumab, cetuximab). Six patients modified the doses of antineoplastic agents due to toxicity not related to raltegravir. During a median follow-up of 67.8 patient-years (median 170 days in concomitant therapy) there was only 1 case of virological failure and no patient discontinued RAL. Geometric mean trough levels of RAL were 143 ng/ml (79–455). There were no opportunistic infections, median CD4 + T-cell count increased by 49 cells/ml and four (13%) patients died during the study (not related to AIDS progression). Conclusions: Our results show that a RAL-based regimen is safe and effective in patients requiring chemotherapy, irrespective of type and of duration of chemotherapy.